Penas e medidas alternativas : caminhos, paisagens, encontros, reflexões - Canal, Fabiana Davel (2012)
Imprisonment became the penalty for excellence in contemporary society. However, we observed that the penalties and alternative measures (LDCs) are increasingly used by the Brazilian legal system, being considered by many as a change in the ways of punishing. They seem indisputable, given the horrors experienced these years that the prison was the only legal form of effective punishment. But the recognition of its importance should not prevent us from problematizing them. So the general objective of this research is to analyze how the penalties and alternative measures carried out in Vitória-ES happen, to determine the existing practices and the effects of compliance with the LDC on the lifestyles of inmates / beneficiaries. Therefore the methodology used was as a field diary, containing our experience in the training course on human rights for people who abide by LDCs and five semistructured interviews with members of that course. Foucault was the one who gave us tools to build our analyses, which are based on archeo genealogy. Through it, we seek to find the things said and lived, the practices built, the truths stated, the institutions used etc. Our analyses show the judicialization of life as an important cog for the increase in LDCs. In the course, we lived many stories, along with those heard in the interviews, we realized that, in relation to a source - in our case, the code dictated by fairness - there is not the only option to fulfill it, but endless ways to live it. So if sometimes the penalties and alternative measures are lived so hard, promoting the total subjection and submission by inmates, in others they act as a problem-solving mode of life, and powerful allies in the construction of different ways of living.